Konsep Adil dalam Poligami Perspektif Muhammad Quraish Shihab dan Amina Wadud - Natriani; Irfan Lewa (Universitas Islam Negeri Alauddin Makassar, 2022)
This article aims to analyze the differences and similarities between Muhammad Quraih Shihab and Aminah Wadud in terms of fair application in polygamy, namely M. Quraish Shibab, argues that polygamy is neither a recommendation nor an obligation to practice polygamy, but an alternative to resolve family problems. Meanwhile, Amina Wadud's opinion about polygamy is not allowed because the reasons that have been believed so far have never been found in the Qur'an. Thus, an important point that can be drawn from Amina Wadud's thinking is an attempt to dismantle old thoughts and old myths built by patriarchal culture. This research is a library research (Library Research). The approach used is descriptive-comparative. Techniques in analyzing data deductively, namely the pattern of studies discussed and studied are general-specific.